Design of a Quality Management System for the Paper Mill Don Bosco, Nuevo Chimbote, Áncash - Perú - Díaz-Batalla, Melina (2022)
The present paper is about a non-experimental research work that was developed in the Don Bosco Paper Mill, a company dedicated to the elaboration of handmade paper products with cotton fiber that seeks to position itself in the national and foreign market with a high-quality product. Thus, to improve competitiveness and ensure the quality of its products, it was proposed to design a Quality Management System (QMS) based on ISO 9001: 2008. To this end, as a starting point, a strategic analysis was prepared to determine the mission, vision, values, and a SWOT analysis. Then, a diagnosis of the company was carried out according to the requirements demanded by ISO 9001:2008, through a checklist. The Quality Cost Survey of the Mexican Institute of Quality Control (IMECCA) was also applied. The results of the diagnosis showed that improvements were required from the organization of support to the assurance of its procedures. According to the ISO 9001:2008 standards, the QMS found was deficient, with 44.58% compliance. For its part, the IMECCA survey indicated that in Don Bosco Paper Mill 11.8% of its sales represent quality costs, specifically in the evaluation and correction of defects. Based on these results, a QMS was designed for the Don Bosco Bin. To this end, it was proposed to reorganize the company into six areas, seven responsible, a Management Committee for the management of the Paper Mill and a Director for decision-making involving important expenses. Finally, the investment budget for the implementation of the QMS in S/. 18616. 13.